MENGENAL POLA ASUH ANAK DIDIK PERSPEKTIF SURAH LUQMAN AYAT 13-15 - Heru Gunawan; Zaianal Efendi Hasibuan (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
This article discusses the concept of children's education according to certain verses in Surah Luqman. The purpose of writing this article is to convey an understanding of the guidelines for children's education contained in Islamic religious teachings, especially those contained in Surah Luqman verses 13-15. The research method used is a literature study of literary sources such as the Al-Qur'an, hadith, tafsir, and previous studies regarding children's education. The results of the study show that these verses contain important guidelines regarding monotheism education, morals, obedience to parents, and children's spiritual independence. It was also stated that the family plays a key role in shaping a child's personality from an early age through informal education. It is hoped that this article can provide a deeper understanding of the concept of children's education according to Islamic understanding, especially those contained in religious teachings through the Al-Qur'an.